Caracterização e modelagem matemática da fração recristalizada de ferrita no aço inoxidável ferrítico AISI 430 durante o processo de deformação a quente em laminador Steckel - Willy Schuwarten Junior (2007)
This work deals with the characterization and mathematical modeling of the ferritic recrystallised fraction in AISI 430 ferritic stainless steel during the hot deformation in a Steckel mill process. A characterization of the thermo mechanical cycle of AISI 430 industrial process from reheating of the plate to annealed coil in box has been presented. A mathematic model was developed in spreadsheet to predict the ferritic recrystallisedfraction during the steel processing. At the same time, is shown the results of a physical simulation by hot torsion. The results obtained by both, mathematical model and physical simulation by hot torsion test, lead to a trend with the industrial process, if compared the levels of average flow tension and the recrystallised fraction of ferrite. The mathematical model and the physical model that were developed can be used for industrial hot rolling process optimization of the AISI 430 steel.The quantification of the ferritic recrystallised fraction in samples, obtained from industrial process, for the model adjustment, was performed with EBSD. Analysis of Microstructure by conventional optical microscopy and also with the use of color attack and polarized light were not satisfactory to separation of fractions of ferrite recrystallised and not recrystallised. Differences in microstructure of the head, body and tail of the AISI 430 strip steel were observed. The mathematic model developed is able to provide trends in the same direction of observed on rolling industrial line. The use of EBSD became possible and reliable the quantification of the ferritic recrystallised fraction. The curves of averageflow tension by hot torsion have the same format of curves derived from the industrial rolling. The microstructures of the hot torsion testes follow the same trends of the microstructures presented by samples got from industrial rolling.